Analisa Pengaruh Variasi Media Pendingin Terhadap Kekerasan dan Kekuatan Tarik Sambungan Las Menggunakan Pola Ayunan Melingkar Pada Baja Carbon Sedang - Susanto, Weldi; Kadir, Kadir; Kadir, Abd. (Teknik Mesin Universitas Halu Oleo, 2020)
Has conducted research on the analysis of the influence of cooling media variations on the hardness and tensile strength of welded joints using circular swing patterns on medium carbon steel. This study aims to determine the effect of cooling media variations on hardness and tensile test using circular swing patterns on medium carbon steel. The method used in this study is that steel is given heat treatment (welding) using 100 amperes, which are then subjected to rapid cooling with oil, air, and water-cooling media. After the welding process and the formation of specimens, tensile testing and hardness testing are done using the Vickers (HVN) method. The results of this study are: (1) the tensile strength welding results obtained on oil cooling media with a value 337.3956 MPa, strain 12.08333 %, elastic modulus 27.948202 MPa, air conditioning media with a voltage value of tensile 470.11347 MPa, strain 13.155557 %, elastic modulus 53.460519 MPa, water cooling media obtained tensile stress 548.165333 MPa, strain 36.6666667 % elastic modulus 15.0436717. (2) The level of violence in both the weld area and the HAZ area did not show a significant difference. The highest hardness is in water cooling where the hardness of 192.35 in the weld area is obtained 194.61 HVN hardness obtained. The lowest hardness occurred in air cooling where 168.65 hardness was obtained in the weld area while for the HAZ area 153.79 HVN hardness was obtained.Keywords: SMAW, circular swing pattern, hardness test, tensile test